A study of hybrid art practices among the artworks of selected Malaysian artists / Valerie Michael and Khairul Aidil Azlin Abd Rahman - Michael, Valerie; Abd Rahman, Khairul Aidil Azlin (Faculty of Art and Design, 2021)
The revolution in art practices has led Malaysian artists to discover greater possibilities in art, especially in terms of media exploration. In this paper, the researchers conducted a study of hybrid art practices among the artworks of selected Malaysian artists. The research objective of this paper is to identify and trace, among the selected artworks, hybrid art practices as a way of creating hybrid artworks. The researchers applied direct observation and extracted the artists' statements for documentation. The results show that most of the artworks applied modern technology and have an element of interaction with the audience. In addition, media exploration has expanded to technological and scientific knowledge. In conclusion, the diversity of media and the discipline have enabled artists to explore more media when producing creative artworks. These collaborations have expanded to produce new findings and allow new perspectives on disciplines in art.